MANAGEMENT TO STRENGTHEN THE COMMUNITY ENTERPRISE IN KHON KAEN PROVINCE - Inbueng, Lakkana; Kunpalin, Poowanida; Toopoj, Poj (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to study the strength management factor and guideline to develop the strength of community in Khon Kaen province. The theoretical study method and in-depth interview were employed as research tools to collect data from 14 enterprise community leaders. The data were analyzed using content analysis which led to model development and was examined the consistency of the empirical data with the theoretical model, and the leaders assessed to be good potential. The results of the study revealed that 1) strength management factor of enterprise community in finance found that it had dividend, saving, and welfare to the society For marketing, it had regular customers, and it also sells product via an online platform. For production, it used community material. For management, there were working capital from funding and appointing committees. For cooperation, they relied on each other to preserve and pass on knowledge to members using local wisdom from generation to generation and joint the group to design new products. For leadership, it had a discussion group to exchange knowledge between members, principles that were applied in management, and potential in operation. Lastly, for government policy, the government promoted the integration of the enterprise community to be certified, registered, and certified the standard of the community’s products. 2) There were three aspects’ results in the guideline to develop the strength of the enterprise community. First, the economic, the community was founded as a joint-owner which was a self-management and had a working capital from internal employment in the community. Second, society, there were a life quality and income development of the community’s members. It also supported skills and developed productivity and income in the community in order to create the strength community. Third, the environment, the amount of material was decreased and encouraged natural resource preservation to use them as a raw material in producing the product by developing the strength of production to reach the global standard in processing product. Building a business network aimed to promote product contribution and expand marketing channels, to strengthen the management capacity in building a network, supporting budget in enterprise community development, and building the cooperation with the relevant organizations systematically